Relationship between Czech windstorms and air temperature. (17th February 2016) - Kašpar, M.; Müller, M.; Crhová, L.; Holtanová, E.; Polášek, J. F.; Pop, L.; Valeriánová, A.
ABSTRACT: The strongest Czech windstorms from 1961 to 2010 were evaluated using a weather extremity index. The index combines the return periods of station wind gusts and the size of the affected area allowing determination of the duration of individual events. Of 50 extreme wind events (EWEs), most were synoptic‐scale windstorms that occurred between the end of October and the beginning of March. However, six EWEs were categorized as the convective‐scale windstorms. Four of the strongest Czech and European windstorms were related to one other (Kyrill, the November 1984 storm, Vivian and Wiebke, and Jeanette). Approximately 90% of the synoptic‐scale windstorms were characterized by strong westerly or northwesterly flow at the 850 hPa level and a north–south temperature gradient at the 500 hPa level. The remaining (rather weaker) synoptic‐scale events were characterized by southerly flow and a west–east temperature gradient at the 850 and 500 hPa levels, respectively. To determine the abnormality of windstorms by season, a weather abnormality index was used to evaluate 50 abnormal wind events (AWEs). Throughout the summer, as well as in half of May and September, AWEs were categorized as the convective‐scale windstorms accompanied by weak 850 hPa winds. Apart from two events with easterly winds, the remaining AWEs were accompanied by winds from the southwest and a strong west–east temperature gradient at the 850 hPa level. Ten of the latter events occurred in the last two ten‐day periods of July and first two ten‐day periods of August. All of the events followed hot episodes, and seven of them followed one of the 25 extreme high‐temperature events. A less pronounced relationship between wind and temperature anomalies was present in the colder half of the year from October to March: three of the strongest Czech EWEs were associated with abnormal high‐temperature events (AHEs).